KARAKTERISTIK ORGANOLEPTIK DAN FISIKOKIMIA MINUMAN SERBUK DAUN KERSEN (Muntingia calabura) DAN DAUN BINAHONG (Anredera cordifolia) DENGAN PEMANIS STEVIA - Ika Dyah Kumalasari; Ayu Larasati (Jurnal Agroindustri, 2023)
Cherry leaves and binahong leaves have the potential to be processed into products in the form of powder drinks that have the potential as antioxidants, such as flavonoids, phenols, polyphenols, alkaloids, saponins and tannins. The purpose of this study was to determine the organoleptic and physico-chemical characteristics of powder drink made from cherry leaves (Muntingia calabura L.) and binahong (Anredera cordifolia) leaves with stevia (Stevia rebaudiana) leaf sweetener. The experimental design used a completely randomized design with two factors, namely the concentration of treatment of cherry leaves and binahong leaves 80%:0% (K1), 60%:20% (K2), 40%:40% (K3), 20%:60% (K4), 0%:80% (K5) with drying temperatures 55℃ (T1) and 60℃ (T2). The parameters in this study were organoleptic characteristic, water content, protein, fat, carbohydrates, antioxidants, total phenol, and solubility. Statistical processing using Two Way Analysis of variances (ANOVA) was continued with the Tukey test at a significant level of 0.05%. The results of the selected formulation K3T1, were significantly different from K3T2. The highest water content was 7.29% (K3T1), the highest fat was 0.46% (K3T2), the highest ash was 10.53% (K3T1), the highest protein was 12.39% (K3T1), the highest carbohydrate was 70.60% (K3T2), the highest %RSA was 75.80% (K3T1), the highest total phenol was 11.60% (K3T1), and the highest solubility was 46.00% (K3T2). The high antioxidant content in the K3T1 formulation can be used as an antioxidant-rich powder drink.